2021
DOI: 10.1101/2021.09.09.459707
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tumor Suppressor p53 Restrains Cancer Cell Dissemination by Modulating Mitochondrial Dynamics

Abstract: Tumor suppressor p53 plays a central role in preventing tumorigenesis. Here, we unravel how p53 modulates mitochondrial dynamics to restrain the metastatic properties of cancer cells. p53 inhibits the mammalian target of rapamycin complex 1 (mTORC1) signaling to attenuate the protein level of mitochondrial fission process 1 (MTFP1), which fosters the pro-fission dynamin-related protein 1 (Drp1) phosphorylation. This regulatory mechanism allows p53 to restrict cell migration and invasion governed by Drp1-mediat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…We have identified a novel role for TAp73 in regulating OPA1 expression and thereby mitochondrial morphology and function. This finding has numerous implications, as the control of mitochondrial dynamics by the p53 family is a key mechanism for the regulation of cell metabolism (including metabolic shifts observed in cancer) (49), tumour cell growth, dissemination (50), and differentiation (51). Indeed, previous evidence has shown that p53 regulates mitochondrial morphology through the transcriptional regulation of MFN2 (52).…”
Section: Discussionmentioning
confidence: 85%
“…We have identified a novel role for TAp73 in regulating OPA1 expression and thereby mitochondrial morphology and function. This finding has numerous implications, as the control of mitochondrial dynamics by the p53 family is a key mechanism for the regulation of cell metabolism (including metabolic shifts observed in cancer) (49), tumour cell growth, dissemination (50), and differentiation (51). Indeed, previous evidence has shown that p53 regulates mitochondrial morphology through the transcriptional regulation of MFN2 (52).…”
Section: Discussionmentioning
confidence: 85%